2001
DOI: 10.1590/s1413-78522001000300003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo sobre a biocompatibilidade da polisulfona sob a forma de particulas e bastões

Abstract: Foi estudada comparativamente a resposta do músculo tríceps sural e reto do abdome de ratos Wistar à implantação da polisulfona (PSU) e do polietileno de ultra alto peso molecular (UHMWPE ) sob a forma de bastões e partículas, por um período de até 52 semanas. Ao final, a PSU foi considerada como tendo a mesma biocompatibilidade do UHMWPE, segundo os critérios utilizados.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Ion-exchange membranes are an important technological tool in many applications, such as desalination, clean energy production, and chemical recovery. These materials demand specific properties, such as high ion conductivity and selectivity, very good chemical and thermal stability, good mechanical properties, and low production cost. , It is common to use polymeric materials in order to achieve most of those requirements. Polysulfone (Psf), well-known for its outstanding chemical and thermal resistance and also mechanical strength, is a perfect base material for creating such membranes. , Moreover, it has been previously reported that Psf is a hydrophobic polymer, compatible with biomolecules such as tissues and blood proteins. …”
Section: Introductionmentioning
confidence: 99%
“…Ion-exchange membranes are an important technological tool in many applications, such as desalination, clean energy production, and chemical recovery. These materials demand specific properties, such as high ion conductivity and selectivity, very good chemical and thermal stability, good mechanical properties, and low production cost. , It is common to use polymeric materials in order to achieve most of those requirements. Polysulfone (Psf), well-known for its outstanding chemical and thermal resistance and also mechanical strength, is a perfect base material for creating such membranes. , Moreover, it has been previously reported that Psf is a hydrophobic polymer, compatible with biomolecules such as tissues and blood proteins. …”
Section: Introductionmentioning
confidence: 99%